Helicobacter pylori in dyspeptic patients in M. Jamil Hospital-Padang - Nasrul Zubir; Dona Elfina; Julius R. Samban (The Indonesian Society for Digestive Endoscopy, 2000)
Objective: Helicobacter pylori infection is probably the most common infection caused by pathogenic bacteria and affects more than half of the world population. These bacteria caused many gastroduodenal pathology such as chronic active gastritis, peptic ulcer and gastric malignancy. This study investigated Helicobacter pylori infections in dyspeptic patients. Materials Methods: Forty dyspeptic patients were examined using upper gastrointestinal endoscopy and biopsy for histopathologic examination. Results: The symptom of the dyspeptic patients were epigastric tenderness (100%). Endoscopic abnormalities were found in 39 (97.5%) cases. The gastric abnormalities were chronic antral gastritis in 24 (60%), esophagitis and gastritis in 7 (17.5%), and gastric ulcer in 3 (7.5%). Twenty four out of 40 patients had anti-Helicobacter pylori positive (60%) and histopathologic examination were positive 18 (45%). The histopathologic examination found atrophy in 18 (45%), MN in 18 (45%), PMN in 18 (45%), and metaplastic in 4 (10%). Conclusion : The prevalence of Helicobacter pylori in dyspeptic patients were 60% (serology) and 45% (histopathology). Keywords: Helicobacter pylori, dyspeptic, serology, histopathology